2017
DOI: 10.1177/1756283x17713879
|View full text |Cite
|
Sign up to set email alerts
|

Current status on the place of FOLFIRINOX in metastatic pancreatic cancer and future directions

Abstract: Pancreatic cancer (PC) incidence rates are rapidly increasing in developed countries, with half the patients being metastatic at diagnosis. For decades, fluorouracil, then gemcitabine regimens were the preferred palliative first-line options for fit patients with metastatic PC. FOLFIRINOX (a combination of bolus and infusional fluorouracil, leucovorin, irinotecan and oxaliplatin) was introduced to clinical practice in 2010 due to the results of the phase II/III trial (PRODIGE 4/ACCORD 11) comparing FOLFIRINOX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…The modified FOLFIRINOX regimen consisted of oxaliplatin 85 mg/m 2 , leucovorin 400 mg/m 2 , irinotecan 150 mg/m 2 , and continuous fluorouracil 2400 mg/m 2 , without bolus fluorouracil. However, mFOLFIRINOX remains a protocol with many side effects, so it could be administered especially to fit patients [22,23], since in the adjuvant setting there are no serological alterations (such as an increase in bilirubin) which may affect the use of irinotecan [24]. Certainly, the choice of adjuvant treatment can also affect the choice of first-line treatment, since the appearance of oxaliplatin neuropathy makes it difficult to subsequently use a combination with nab-paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…The modified FOLFIRINOX regimen consisted of oxaliplatin 85 mg/m 2 , leucovorin 400 mg/m 2 , irinotecan 150 mg/m 2 , and continuous fluorouracil 2400 mg/m 2 , without bolus fluorouracil. However, mFOLFIRINOX remains a protocol with many side effects, so it could be administered especially to fit patients [22,23], since in the adjuvant setting there are no serological alterations (such as an increase in bilirubin) which may affect the use of irinotecan [24]. Certainly, the choice of adjuvant treatment can also affect the choice of first-line treatment, since the appearance of oxaliplatin neuropathy makes it difficult to subsequently use a combination with nab-paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that extracellular matrix components like collagen can influence clonogenic tumor growth, tumor initiation, and invasion of PDAC due to activation of the FAK signaling pathway [26,27] . Additionally, a hypoxic tumor microenvironment is known to promote the conversion of non-CSC to CSC populations in PDAC [8] . These data corroborate with observations that the CSCs within the tumor are the cells' survival advantage, capable of living under stress conditions and to express resistance to cancer therapies.…”
Section: Pcscsmentioning
confidence: 99%
“…Recent evidence shows that using FOLFIRINOX (leucovorin, fluorouracil, irinotecan, oxaliplatin) in PDAC patients was more effective than GEM as it demonstrated longer survival in pancreatic cancer patients (11.1 months vs. 6.8 months) [6,7] . Resistance to apoptosis is a common feature of PDAC and a major reason why this devastating disease is resistant to various treatment strategies including GEM and FOLFIRINOX [8] . Another major problem limiting our ability to treat PDAC is the existence of rare populations of pancreatic cancer stem cells (PCSCs) or cancer-initiating cells in pancreatic tumors; PCSCs may represent sub-populations of tumor cells resistant to therapy which are most crucial for driving invasive tumor growth [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy combinations, such as FOLFIRINOX and gemcitabine plus nabpaclitaxel have significantly increased the overall survival of PC patients with advanced diseases (Mcbride et al, 2017;Nguyen et al, 2017). However, FOLFIRINOX has recently been associated with increased toxicity, mainly febrile neutropenia and diarrhea (Lambert et al, 2017). Numerous studies have unraveled the common molecular alterations occurring in PC, such as mutations in Kras, p53, and BRCA1 (Nag et al, 2013;Cicenas et al, 2017;Waters and Der, 2018), aberrant activation of wnt/bcatenin signaling and keap1/Nrf2 signaling (Qin et al, 2018;Kuo et al, 2019;Qin et al, 2019), and amplification and overexpression of MDM2, cyclin D1, USP7, and MDR1 (Qie and Diehl, 2016;Robey et al, 2018;Wang et al, 2019b;Dong et al, 2020;Qi et al, 2020), which play critical roles in the initiation, progression, metastasis, and chemoresistance of PC.…”
Section: Introductionmentioning
confidence: 99%